Enhancement of reproductive performance in postpartum Murrah buffaloes treated with prostaglandin and gonadotrophin releasing hormone - RK Malik; Pardeep Singh; IS Lohan; RK Tuli (Journal of Livestock Biodiversity, 2025)
Fifty postpartum buffaloes were divided into five groups, treatments (T1, T2, T3, T4) and one control (T5). Prostaglandin (Lutalyse) and gonadotrophin releasing hormone (receptal) were used in combination or alone to induce cyclicity. All the animals were palpated per rectum manually, on days 10, 15, 27, 35, 45, 50 and 60 postpartum to note reproductive status. Treatments (T1, T2, and T3) differed significantly (P<0.01) to T4 and T5 treatments. There was no significant difference between T4 and T5. Medium and large sized follicles were observed on days 10 and 15 postpartum in treatment groups and on day 20 in control group. In treated groups (37/38) first heat appeared within 25-111 days and in control group (9/12) within 25-104 days postpartum. Effect of hormonal treatments on occurrence of first heat and service period significantly differed as compared to control groups. Service period was lowest in November calvers. Month of calving and parity had no significant. effect on involution of uterus periods. Primiparous animals had highest interval between calving to first heat and conception.